Comparative trends and effectiveness of amlodipine and nifedipine as oral antihypertensives in preeclampsia management - Awaludin, Adila; Rahmawati, Ayu; Annisa, Annisa; Septiani Agustien, Gina (Pharmaciana, 2025)
The use of amlodipine in preeclampsia remains limited as it is not a treatment option officially. Whereas amlodipine's long half-life allows less frequent dosing in preeclampsia patients, potentially improving preeclampsia treatment more efficiently compared to nifedipine (standard medicine). Ensuring the effectiveness of amlodipine for preeclampsia is essential for optimizing delivery outcomes, in addition to efficiency aspects. However, the effectiveness study of amlodipine in preeclampsia patients is still not definitively known. This study aims to determine the prescription trends and effectiveness of amlodipine as an antihypertensive in preeclampsia. The study used a cross-sectional approach conducted at a one of the secondary healthcare facilities in Tasikmalaya, utilizing medical records from January 2019 to December 2023. The data were analyzed using Chi-Square test to determine the trends using and effectiveness of amlodipine compared to nifedipine in controlling blood pressure in preeclampsia. The study shows that the trends using of amlodipine in preeclampsia is decreasing over the past 5 years (2019 to 2023). This phenomenon may be influenced by limited evidence, established clinical practice guidelines, and priority of drug use. There was no significant difference in effectiveness of amlodipine compared to nifedipine in single therapy (p= 0.698) or dual therapy (p=0.1). Furthermore, the study found that amlodipine and nifedipine exhibited comparable effectiveness in controlling blood pressure in preeclampsia. Therefore, amlodipine may be considered as an alternative antihypertensive option for controlling blood pressure in preeclampsia.